The light beyond - Moody, Raymond A; Perry, Paul; Greeley, Andrew M (Bantam books, 1989)
'The Light Beyond' is based on more than a thousand case studies of adults and children who clinically reached the point of death and survived, as well as amazing new research. It shows the many striking similarities shared by all near-death experiences (NDEs), and uncovers secrets and opens the doors to a powerful message of love from the frontier between life and death. Zdroj: Web goodreads.com
Keywords: Attitude to Death; výzkum; humanitní vědy a umění; postoj ke smrti; filozofie; Religion; náboženství; Philosophy; Research